Pharmacokinetics, Safety, and Tolerability of a 2-Month Dose Interval Regimen of the Long-Acting Injectable Antipsychotic Aripiprazole Lauroxil: Results From a 44-Week Phase I Study - Weiden, Peter J. (CNS Drugs, 2020)
BACKGROUND: Aripiprazole lauroxil (AL) is a long-acting injectable antipsychotic approved for treatment of schizophrenia in adults. Approved AL doses and dosing regimens include 441 mg monthly, 662 mg monthly, and 882 mg monthly or every 6 weeks (q6wk), as well as the most recently approved dose, 1064 mg, administered every 2 months. OBJECTIVE: Pharmacokinetics, safety, and tolerability of an AL regimen with a dose interval of every 2 months (1064 mg) were compared with two other regimens available as monthly and q6wk options. METHODS: This study evaluated pharmacokinetics of AL given at a higher dosage strength (1064 mg) and at a longer dose interval (every 8 weeks [q8wk]) than previously studied. Patients with schizophrenia or schizoaffective disorder entering this 44-week, phase I, open-label, multicenter study had no recent exposure to aripiprazole and were maintained on other oral antipsychotics throughout the study. Patients were randomized to one of three AL dose regimens for 24 weeks (four 1064-mg injections [q8wk], five 882-mg injections [q6wk], or seven 441-mg injections [q4wk], with the last AL exposure at week 24). Oral aripiprazole was prohibited. Patients were followed for an additional 20 weeks to assess terminal aripiprazole plasma concentrations and ongoing safety. Plasma concentration samples were obtained at regular intervals to provide pharmacokinetic data for the duration of AL exposure and to measure persistence of plasma aripiprazole concentrations after AL discontinuation. RESULTS: Eligible patients received AL 1064 mg q8wk (n = 35), 882 mg q6wk (n = 34), or 441 mg q4wk (n = 35). Overall, 103/104 (99.0%) patients were taking concomitant non-aripiprazole oral antipsychotic medications during the study. All three AL dose regimens provided continuous exposure to aripiprazole. Mean aripiprazole concentrations from the 1064-mg q8wk regimen were comparable to the 882-mg q6wk regimen and higher than the 441-mg q4wk regimen. Overall incidence by group of any adverse events (AEs) throughout the study was 68.6% (1064 mg q8wk), 50.0% (882 mg q6wk), and 65.7% (441 mg q4wk). The most common AE across regimens was injection-site pain (range 8.6%–11.4%). Serious AEs were reported by eight patients (all but one [increased psychosis in one patient, 441-mg q4wk group] considered unrelated to study drug). Discontinuations due to AEs were reported for 2.9%, 11.8%, and 5.7% of patients receiving the 8-, 6-, and 4-week regimens, respectively. AEs of akathisia, dyskinesia, and dystonia occurred in 2.9%, 8.6%, and 5.7% of patients in the 1064-mg q8wk group, 8.8%, 0%, and 2.9% in the 882-mg q6wk group, and 8.6%, 0%, and 0% in the 441-mg q4wk group, respectively. CONCLUSIONS: AL 1064 mg q8wk provided continuous exposure to aripiprazole throughout the 8-week dosing interval and had a safety profile consistent with the 4- and 6-week regimens. These findings were used to support FDA approval of the 1064-mg dose administered every 2 months. REGISTRATION: Clinicaltrials.gov: NCT02320032